Gradient cement pastes with efficient energy dissipation and electromagnetic wave absorption - Yihao Xiao; Yajing Miao; Xin Zhang; Yahui Xue (Communications Engineering)
Abstract Modern engineering demands materials that combine mechanical robustness with effective electromagnetic wave absorption, driven by advancements in wireless communication, radar technologies, and smart infrastructure. Here, we construct a gradient cement paste by layering cement slurries with varying concentrations of carbon nanotubes. This gradient design enhances toughness and impact resistance by optimizing microstructural features and interfacial interactions, which facilitate efficient load transfer and stress delocalization. Additionally, the gradient structure improves electromagnetic wave absorption performance through optimized impedance matching and multiple electromagnetic loss mechanisms, including multiple reflections, scattering, and reabsorption of electromagnetic waves within the material. These synergistic properties position gradient cement pastes as promising high-performance, multifunctional materials for mitigating electromagnetic pollution and advancing next-generation infrastructure.